KEY PRINCIPLES OF RURAL TOURISM HOUSEHOLDS DEVELOPMENT STRATEGY - CASE STUDY OF VOJVODINA - Košić, Kristina; Demirović, Dunja; Pejanović, Radovan; Lazić, Lazar; Stamenković, Igor (Economics of Agriculture, 2015)
The subject of the paper is the analysis of the condition and perspectives of the development of rural tourism in households of Vojvodina. Vojvodina with its natural and social resources qualifes for a position within the developed rural tourism regions. However, rural tourism product in Vojvodina has not been holding an appropriate position at the market. For the aim of determining principles and factors for successful rural tourism, questionnaire has been formed, which has been conducted among 70 country households involved in tourism. In order to achieve the best possible position at the international market, Vojvodina needs to apply the model of development that would ensure competitive advantage regarding similar destinations. Essential activities for improving service quality in rural tourism are: to improve the quality of accommodation facilities, to educate population with the aim of achieving higher service quality, to establish and apply criteria for standardization and service quality in rural tourism in Vojvodina and to intensify promotion at domestic and international market.